Music From the Very Beginning—A Neuroscience-Based Framework for Music as Therapy for Preterm Infants and Their Parents - Haslbeck, Friederike Barbara; Bassler, Dirk (Frontiers in Behavioral Neuroscience, 2018)
Human and animal studies demonstrate that early auditory experiences influence brain development. The findings are particularly crucial following preterm birth as the plasticity of auditory regions, and cortex development are heavily dependent on the quality of auditory stimulation. Brain maturation in preterm infants may be affected among other things by the overwhelming auditory environment of the neonatal intensive care unit (NICU). Conversely, auditory deprivation, (e.g., the lack of the regular intrauterine rhythms of the maternal heartbeat and the maternal voice) may also have an impact on brain maturation. Therefore, a nurturing enrichment of the auditory environment for preterm infants is warranted. Creative music therapy (CMT) addresses these demands by offering infant-directed singing in lullaby-style that is continually adapted to the neonate’s needs. The therapeutic approach is tailored to the individual developmental stage, entrained to the breathing rhythm, and adapted to the subtle expressions of the newborn. Not only the therapist and the neonate but also the parents play a role in CMT. In this article, we describe how to apply music therapy in a neonatal intensive care environment to support very preterm infants and their families. We speculate that the enriched musical experience may promote brain development and we critically discuss the available evidence in support of our assumption.